CONSEQUENCES OF THE LAW OF DOMINATION AND DEVELOPMENT WAQF LAND WITHOUT RIGHTS - Danial Syah (LPPM YPITI, 2026)
Land control without rights is a land control carried out by a person or legal entity to enjoy or use land that is not their own land without rights and also against the law. The practice of waqf that occurs in people's lives is not yet fully carried out in an orderly and efficient manner, so that in various cases waqf assets are not maintained properly, are abandoned, are transferred to third parties or to heirs in a way that is against the law. This situation is only due to the nazhir's negligence or inability to manage and develop waqf assets. This is also due to the attitude of the public who do not care or understand the status of waqf property which should be protected for the sake of general welfare in accordance with the aims, functions and designation of waqf. As a legal consequence of using land rights by parties who do not have rights to waqf land, this action is an unlawful act.